Robust Lessons about Practical Early Warning Systems - Daniela Beckmann; Lukas Menkhoff; Katja Sawischlewski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
Early warning systems (EWSs) are subject to restrictions that apply to exchange rates in general: fundamentals matter but their influence is small and unstable. Despite this limitation four major lessons emerge: First, EWSs have robust forecasting power and thus help policy-makers to prevent crises. Second, policy-makers must decide about some EWSs' elements, such as the sensitivity of the forecasts. Third, EWSs' performance is increased by taking a logit model, shorter samples and a regional approach. Fourth, the finding of contagion may motivate policy to shield its economy against inefficient international financial markets.
Keywords: F31; F37; F33; 330; early warning system; currency crises; emerging markets